2002
DOI: 10.2307/3071914
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove Isotopic (δ 15 N and δ 13 C) Fractionation across a Nitrogen vs. Phosphorus Limitation Gradient

Abstract: Mangrove islands in Belize are characterized by a unique switching from nitrogen (N) to phosphorus (P) limitation to tree growth from shoreline to interior. Fertilization has previously shown that Rhizophora mangle (red mangrove) fringe trees (5-6 m tall) growing along the shoreline are N limited; dwarf trees (Յ1.5 m tall) in the forest interior are P limited; and transition trees (2-4 m tall) are co-limited by both N and P. Growth patterns paralleled a landward decrease in soil flushing by tides and an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
140
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(158 citation statements)
references
References 39 publications
17
140
0
1
Order By: Relevance
“…In general, a decrease in soil water potential will lead to an increase in the d 13 C value (Guy, Reid & Krouse 1980). Several studies have further demonstrated a relationship between mangrove growth forms (expressed in tree height) and carbon isotopic composition of leaves, with tall mangrove stands showing lower d 13 C values than scrub mangroves (Lin & Sternberg 1992b;Kao & Chang 1998;McKee et al . 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, a decrease in soil water potential will lead to an increase in the d 13 C value (Guy, Reid & Krouse 1980). Several studies have further demonstrated a relationship between mangrove growth forms (expressed in tree height) and carbon isotopic composition of leaves, with tall mangrove stands showing lower d 13 C values than scrub mangroves (Lin & Sternberg 1992b;Kao & Chang 1998;McKee et al . 2002).…”
Section: Introductionmentioning
confidence: 99%
“…2002). Although, the growth forms are the result of a synergistic effect of different stress factors, such as soil salinity, sulphide concentration and nutrient levels (Lin & Sternberg 1992a;McKee et al . 2002), only salinity affected the c i / c a .…”
Section: Introductionmentioning
confidence: 99%
“…Several important contributions to an understanding of nutrient production, cycling, limitation, effects on organisms, and related ecophysiological phenomena have already been published (Feller et al, 2002 Lovelock et al, 2006; Cheeseman and Lovelock, 2004), but many more are expected in the near future now that the fi eldwork phase of the Biocomplexity Program has come to a conclusion. One surprising discovery, in a complementary project by CCRE postdoctoral fellow Amy Erickson, was that the intertidal tree crab Aratus, long thought to be a mangrove leaf eater, actually prefers an animal diet if given a choice (Erickson et al, 2008).…”
Section: • S M I T H S O N I a N C O N T R I B U T I O N S T O T H E mentioning
confidence: 99%
“…However, rather than solely a function of marine P inputs, very high precipitation has resulted in a raised bog in the interior wetland, resulting in P limitation. Interestingly, increased P limitation occurring from the coast to the interior of Panama appears to be a key driver of plant and bacterial community structure, suggesting this upside-down phenomenon is not restricted to carbonate wetlands, but perhaps a more common feature of subtropical and tropical coastal wetlands (Anderson 1983, Bridgham and Richardson 1993, Chen and Twilley 1999, Paludan and Morris 1999, McKee et al 2002. These results suggest that the shift towards P limitation found in a coastal Panama peatland was a developmental characteristic associated with ombrotrophic conditions that developed as hydrologic inputs became dominated by precipitation (Anderson 1964(Anderson , 1983.…”
Section: Are All Karstic Coastal Systems and Wetlands Biogeochemicallmentioning
confidence: 99%